PENDEKATAN BIONOMI DALAM PENGELOLAAN KAWASAN KONSERVASI LAUT KABUPATEN RAJA AMPAT, PROVINSI PAPUA BARAT - Eny Budi Sri Haryani; Akhmad Fauzi; Daniel R. Monintja (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2010)
Raja Ampat Regency in West Papua Province has abundance natural fishery resources. Marine Protected Area (MPA) has been established in marine areas of Raja Ampat Regency. To better manage of MPA is required with measureable parameters and clear indicators. To decide the indicator can be conducted by bioeconomic model approach. The results of research show that the establishment of MPA will increase harvest level and revenue. But â€œbigger is betterâ€ couldâ€™nt be adopted for the development of MPA. There is an optimal MPA size will contribute for increasing yields and revenue and can reduce the level of effort.